1969
DOI: 10.1126/science.164.3878.436
|View full text |Cite
|
Sign up to set email alerts
|

Serum C′3 Lytic System in Patients with Glomerulonephritis

Abstract: The serums of patients with hypocomplementemic glomerulonephritis contain a substance that combines with a normal serum cofactor in the presence of magnesium ion to specifically cleave the third component of complement. This lysis of C'3 is 80 to 90 percent complete in 20 minutes at 37 degrees C and pH 7. Neither the nephritic factor nor its cofactor is identifiable with the complement system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

1972
1972
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(80 citation statements)
references
References 7 publications
1
78
0
1
Order By: Relevance
“…An anti-factor H miniantibody consisting of lambda light-chains, which inhibited factor H complement regulatory activity, was identified in a DDD patient (Meri et al, 1992;Jokiranta et al, 1999). C3 nephritic factor (C3NeF), an antibody against the C3bBb convertase (Spitzer et al, 1969), is found in 50-80% of DDD patients (Schwertz et al, 2001;Appel et al, 2005). C3NeF binds to a neoepitope on the newly assembled C3bBb, increases the half-life of the convertase against both intrinsic and extrinsic, factor H-mediated, decay and thus enhances C3 consumption (Daha et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…An anti-factor H miniantibody consisting of lambda light-chains, which inhibited factor H complement regulatory activity, was identified in a DDD patient (Meri et al, 1992;Jokiranta et al, 1999). C3 nephritic factor (C3NeF), an antibody against the C3bBb convertase (Spitzer et al, 1969), is found in 50-80% of DDD patients (Schwertz et al, 2001;Appel et al, 2005). C3NeF binds to a neoepitope on the newly assembled C3bBb, increases the half-life of the convertase against both intrinsic and extrinsic, factor H-mediated, decay and thus enhances C3 consumption (Daha et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in humans further suggest that the generation of C5a is, by itself, insufficient to produce ARDS (58). Similarly, systemic activation of complement in patients with nephritis due to nephritic factor (59) has not been shown to lead to lung injury. Taken together, these data imply the involvement of multiple factors, including the generation of complementderived chemotactic factors, in the pathogenesis of ARDS.…”
Section: Neutrophil-mediated Endothelial Injury 1239mentioning
confidence: 99%
“…First identified in 1969 by Spitzer et al (12), C3Nefs were described as a substance in serum that increases AP activity from basal "tick-over" levels. Tick-over is the process by which hydrolysis of a reactive thioester in C3 generates small amounts of an initial C3 convertase called C3(H 2 O)Bb.…”
Section: Introductionmentioning
confidence: 99%